2017
DOI: 10.1159/000454821
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>WT1 </i></b>Haploinsufficiency Supports Milder Renal Manifestation in Two Patients with Denys-Drash Syndrome

Abstract: Denys-Drash syndrome (DDS) is characterized by nephropathy, genital abnormalities, and predisposition to Wilms' tumor. DDS patients usually present heterozygous de novo germline WT1 mutations. The WT1 gene comprises 10 exons encoding the N-terminal transactivation and the C-terminal DNA-binding regions. Two unrelated patients with genital ambiguity and Wilms' tumor were analyzed by sequencing of the WT1 gene, and 3 mutations in exon 1 were identified of which 2 are novel. Patient 1 carried a c.555delC mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, much phenotypic variability is seen in patients with WT1 variants, making it difficult to establish a genotype-phenotype correlation [Koziell and Grundy, 1999]. Pathogenic allelic variations in the first exon of WT1 play a causative role in WT1 haploinsufficiency and the development of DDS features with mild renal manifestations [Guaragna et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, much phenotypic variability is seen in patients with WT1 variants, making it difficult to establish a genotype-phenotype correlation [Koziell and Grundy, 1999]. Pathogenic allelic variations in the first exon of WT1 play a causative role in WT1 haploinsufficiency and the development of DDS features with mild renal manifestations [Guaragna et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the most severe renal phenotype in patients with WT1 missense variants is related to a dominant-negative effect exerted by the mutant WT1 protein, blocking the action of the corresponding wild-type protein. However, the milder renal disease phenotype is associated with the dosage effect of truncated WT1 proteins [Pelletier et al, 1991;Guaragna et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…[25] In clinical manifestations of DDS, mutations in other initial exons of the 11p13 locus are less common. [20,31,32] We detected a new mutation in exon 7 encoding the first zincfinger protein. Bruening et al described a case of a mutation in exon 7 in a female patient with nephropathy, but without malignant tumor or DSD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] In clinical manifestations of DDS, mutations in other initial exons of the 11p13 locus are less common. [ 20 , 31 , 32 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation